Glycemic Status, Metabolic Syndrome, and Cardiovascular Risk in Children - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2011)
The metabolic syndrome and adult manifestation of prediabetes and diabetes are major public health problems that begin in childhood. Prevention must be considered as a serious public health issue. Health education and health promotion of school children needs incorporation as a community effort.
Keywords: Obesity; Diabetes; Cardiovascular; Risk factor; TYPE-2 DIABETES-MELLITUS; INTIMA-MEDIA THICKNESS; SYNDROME SYNDROME-X; YOUNG-ADULTS; INSULIN-RESISTANCE; BLOOD-PRESSURE; RACIAL-DIFFERENCES; CAROTID-ARTERY; BOGALUSA; CHILDHOOD